2015
DOI: 10.4049/jimmunol.1401364
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Mouse P2Y4 Nucleotide Receptor Protects against Myocardial Infarction through Endothelin-1 Downregulation

Abstract: Nucleotides are released in the heart under pathological conditions, but little is known about their contribution to cardiac inflammation. The present study defines the P2Y4 nucleotide receptor, expressed on cardiac microvascular endothelial cells and involved in postnatal heart development, as an important regulator of the inflammatory response to cardiac ischemia. P2Y4-null mice displayed smaller infarcts in the left descending artery ligation model, as well as reduced neutrophil infiltration and fibrosis. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
(95 reference statements)
1
30
0
Order By: Relevance
“…Despite their overlapping spheres of influence, information on potential interplay between renal P2 and ET receptors is rare. The interaction between ET-1 and P2 signaling systems has been also demonstrated in extrarenal tissues (1,4,31,35). Our current findings demonstrate that activation of medullary P2 receptors promotes ET-1-dependent natriuresis in OVX rats, similar to male rats (23).…”
Section: Discussionsupporting
confidence: 74%
“…Despite their overlapping spheres of influence, information on potential interplay between renal P2 and ET receptors is rare. The interaction between ET-1 and P2 signaling systems has been also demonstrated in extrarenal tissues (1,4,31,35). Our current findings demonstrate that activation of medullary P2 receptors promotes ET-1-dependent natriuresis in OVX rats, similar to male rats (23).…”
Section: Discussionsupporting
confidence: 74%
“…Cardiac Echography Experiments-Cardiac echography experiments were assessed as previously described (5). Briefly, transthoracic echography was performed on anesthetized mice (1% isoflurane), using a Vevo 2100 system equipped with a 40 MHz transducer (Visualsonics, Toronto, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Another UTP receptor, P2Y 4 , plays an important role in the heart: P2Y 4 knock-out (KO) mice display reduced cardiac angiogenesis and cardiac postnatal development (3), as well as lower exercise capacity and reduced exercise-induced cardiac hypertrophy (4). More recently, it has been shown that P2Y 4 KO mice display lower infarct size and reduced cardiac inflammation and fibrosis in a model of ligation of the left anterior descending artery (5). The study of the role of P2Y 6 UDP receptor in the heart has also been initiated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in oxygen free radicals in heart failure patients leads to EC dysfunction, which causes further deterioration of cardiac function, forming a vicious cycle (Horckmans et al, 2015). Vascular ECs also interact with platelets, white blood cells, and blood vessels and can control the growth of blood vessels.…”
Section: Discussionmentioning
confidence: 99%